Mites (Acari, Mesostigmata) from rock cracks and crevices in rock labirynths in the Stołowe Mountains National Park (SW Poland) - KAMCZYC, JACEK; SKORUPSKI, MACIEJ (Biological Letters, 2015)
The aim of this study was to recognize the species composition of soil mites of the order Mesostigmata in the soil/litter collected from rock cracks and crevices in Szczeliniec Wielki and Błędne Skały rock labirynths in the area of the Stołowe Mountains National Park (part of the Sudetes in SW Poland). Overall, 27 species were identified from 41 samples collected between September 2001 and August 2002. The most numerous species in this study were Veigaia nemorensis, Leptogamasus cristulifer, and Gamasellus montanus. Our study has also confirmed the occurrence or rare mite species, such as Veigaia mollis and Paragamasus insertus. Additionally, 5 mite species were recorded as new to the fauna of this Park: Vulgarogamasus remberti, Macrocheles tardus, Pachylaelaps vexillifer, Iphidosoma physogastris, and Dendrolaelaps (Punctodendrolaelaps) eichhorni.